METHODS OF TEACHING NATURAL SCIENCES TO PRIMARY SCHOOL PUPILS ON THE BASIS OF A COMPETENT - Ochilov Fariddun Izatulloyevich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Annotation. The article is dedicated to the problem methods of teaching natural sciences to primary school pupils on the basis of a competent. Competences are manifested in the form of basic and scientific competencies. These competencies always complement each other and contribute to the formation of practical activities. Basic and scientific competencies are general and specific. They are: 1. Basic competencies are competencies specific to all subjects. 2. Competences related to science, ie competencies specific to a subject. In particular, the special competencies formed in the lessons "The world around us" and "Natural sciences". Thus, the main goal of the competency approach is to form students who are well-developed, creatively active, able to have a conscious attitude to the environment, love nature and preserve its riches. Development of recommendations and developments aimed at teaching pupils natural sciences on the basis of a competent approach in the lessons "The world around us" and "Natural sciences". Organization of seminars, trainings, round tables for primary school teachers to improve their methodological skills in the organization of lessons "The world around us" and "Natural science" on the basis of a competent approach